2021
DOI: 10.1155/2021/9968691
|View full text |Cite|
|
Sign up to set email alerts
|

Model of Human Tongue Squamous Cell Lines Stably Transfected with Human Papillomavirus (HPV)16 E6 and E7 Genes and Biological Characteristic Analysis

Abstract: Background. Human tongue squamous cell carcinoma (TSCC) is the most common oral cancer with the highest human papillomavirus (HPV) infection rate in oral cancer. The purpose of this study was to research the correlation between HPV and TSCC. Method. Plasmid pEGFP/HPV16 E6E7 and plasmid pEGFP/no HPV16 E6E7 were constructed. TSCC cell lines SCC9 and SCC15 were infected by liposome transfection and would be highly selected by antibiotic. Fluorescence imaging, PCR, and Western blot were used to detect the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Ectopic transfection of HPV16 E6/E7 enhanced cell proliferation in tongue cancer cell lines 28 . Genetic deletion of HPV16 E7 causes inhibition of cell proliferation in HPV16‐positive oral cancer cell lines 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectopic transfection of HPV16 E6/E7 enhanced cell proliferation in tongue cancer cell lines 28 . Genetic deletion of HPV16 E7 causes inhibition of cell proliferation in HPV16‐positive oral cancer cell lines 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 5-FU-induced LDH activity was significantly Ectopic transfection of HPV16 E6/E7 enhanced cell proliferation in tongue cancer cell lines. 28 Genetic deletion of HPV16 E7 causes inhibition of cell proliferation in HPV16-positive oral cancer cell lines. 29 In this study, we found that HPV16 E6/E7 knockdown attenuated cell proliferation in HPV16-positive UM-SCC 104 cells.…”
Section: Impact Of Autophagy Inhibitor On 5-fuinduced Cell Death In H...mentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%